Frame Analysis on LGBTQ+ Spaces in Japan : Case Pride Center Osaka and Pride House Tokyo - Mikkonen, Pyry (My University, 2025)
This thesis presents through two case studies how centres such as Pride Center Osaka (PCO) and Pride House Tokyo (PHT) create LGBTQ+ inclusive space in Japan. The aim of this research is to inspect the “injustice frame” (Gamson, 1995; Benford & Snow, 2000), which defines the perceived unjust issues towards the “victims” that the social movement is advocating change for, namely the adversities that LGBTQ+ individuals face in Japanese society. In addition, this research studies how the social movement, in this case LGBTQ+ movement and the LGBTQ+ centres in Japan tackle these adversities in their operation. The methods used in this research are online research and frame analysis. The data used in this research are a list of challenges faced by LGBTQ+ people in Japanese society provided by an organisation J-ALL, an online conference video by PCO and a pdf guidebook by PHT. The difficulties faced by LGBTQ+ people in Japan encompass multiple facets of life, ranging from school life to the workplace and from childhood to elderly age. The centres aim to tackle these difficulties through individual consultation support, but also offer a space for interaction. The centres fit the criteria for “alternative space” in the way that they offer space for the LGBTQ+ social movement to first withdraw to, share their experiences, be empowered and then return back into the broader society to create inclusion. The centres operate in a way of amplifying voices of LGBTQ+ community and they serve as networking hubs, information disseminators and knowledge archives that aim to broaden LGBTQ+ inclusion and visibility. LGBTQ+ allies and other stakeholders are important in this process of spreading understanding. This study is tied to the contemporary discourses of transgender rights and equal marriage rights, as well as the enactment of the “LGBT Understanding Law” in Japan.
Keywords: LGBTQ+, sexual orientation, gender identity, Japan, frame analysis, alternative space, inclusion, inclusive, safe space, consultation support, discrimination, empowerment, SOGIESC, social movement